Art of logic: How to make sense in a world that doesn't - Cheng, Eugenia (London: Profile Books Ltd., 2019)
"In a world where fake news stories change election outcomes, has rationality become futile? In The Art of Logic in an Illogical World, Eugenia Cheng throws a lifeline to readers drowning in the illogic of contemporary life. Cheng is a mathematician, so she knows how to make an airtight argument. But even for her, logic sometimes falls prey to emotion, which is why she still fears flying and eats more cookies than she should. If a mathematician can't be logical, what are we to do? In this book, Cheng reveals the inner workings and limitations of logic, and explains why alogic--for example, emotion--is vital to how we think and communicate. Cheng shows us how to use logic and alogic together to navigate a world awash in bigotry, mansplaining, and manipulative memes. Insightful, useful, and funny, this essential book is for anyone who wants to think more clearly."--
The power of logic: Why logic? ; What logic is ; The directionality of logic ; Opposites and falsehoods ; Blame and responsibility ; Relationships ; How to be right -- The limits of logic: Truth and humans ; Paradoxes ; Where logic can't help us -- Beyond logic: Axioms ; Fine lines and gray areas ; Analogies ; Equivalence ; Emotions ; Intelligence and rationality.
Includes index.
Keywords: Logic, Symbolic and mathematical; Logic -- Popular works; Reasoning -- Popular works; Thought and thinking -- Popular works; Logic; Reasoning; Nonfiction